Rituals of recognition: Interactions and interaction rules in sheltered workshops in the Netherlands. Issue 4 (2nd October 2018) - Sebrechts, Melissa; Tonkens, Evelien; Bröer, Christian
ABSTRACT: Recent decades have witnessed mounting attention to the theme of recognition, both in public policy and in the academic world. Scholarly debate on recognition is dominated by philosophers, while the policy debate is dominated by political and educational perspectives. A sociological perspective has scarcely been developed. In this article, we approach recognition as a sociological phenomenon with the aid of Collins' theory of Interaction Ritual Chains. Our research is located in three Dutch sheltered workshops that aim to provide recognition through work to young men with mild intellectual disabilities. While Collins provides an interesting interactional perspective to distinguish between different situations of recognition, we add an institutional dimension by showing how individualising labour-market policies and care practices articulate a set of 'interaction rules' that encourage some recognition rituals and foreclose others. This demonstrates the importance of a sociological contribution to the debate on recognition, and points to 'unintended consequences' of policies that aim to strengthen recognition in ways that in fact cannot be achieved by those involved. Such a sociological perspective can bring out more practical and nuanced accounts of recognition, and enrich both scholarly and policy debates on this topic.